Malondialdehyde, glutathione and nitric oxide levels in patients with Enterobius vermicularis infection - Kiran, Tu?ba Raika; Karaman, Ülkü; Çolak, Cemil; Bay Karabulut, Aysun; Daldal, Nilgün (My University, 2010)
The aim of this study was to investigate the levels of malondialdehyde (MDA) and nitric oxide (NO) which are indicators of oxidative stress and also the level of glutathione (GSH) which is an antioxidant molecule, in patients with Enterobius vermicularis infection. A total of 41 patients (mean age: 36.4 years; 31 were male) and 40 healthy controls (mean age: 40.2 years; 28 were male) were included to the study. None of the patients and controls have had history of hormone/steroid drug use, smoking and alcoholism. The mean level of GSH in patient and control groups were found 1.17 ± 0.02 ?mol/l and 2.49 ± 0.10 ?mol/l; MDA 26.97 ± 2.06 ?mol/l and 19.47 ± 2.25 ?mol/l NO 20.74 ± 0.60 ?mol/dl and 17.83 ± 0.50 ?mol/dl, respectively. The mean GSH level in patient group was statistically significantly lower (p< 0.05) than controls, while the mean MDA and NO levels were statistically significantly higher (p< 0.05). These results indicated that the consumption of GSH was increased due to the severity of oxidative stress in patients infected with E.vermicularis. Detailed experimental and clinical studies are required to enlighten the relation of GSH in the pathogenesis of E.vermicularis infection. Since oxidative stress is increased during enterobiosis, the use of antioxidant agents (e.g. vitamins C and E) for the supportive treatment deserves evaluation.
Enterobius vermicularis i?le enfekte hastalarda malondi?aldehi? d, glutatyon ve ni?tri?k oksi?t düzeyleri?
Keywords: Enterobius vermicularis; Glutathione; Malondialdehyde; Nitric oxide